Gender dan Industri Kecil Agro di Pedesaan Tasikmalaya - Charina, Anne; Mukti, Gema Wibawa; Kusumo, Rani Andriani Budi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
While the number of female-gendered small industry entrepreneurs is growing, research in this area has not kept pace. This article critically reviews the current situation of women entrepreneurs in rural areas. We analyze the social, cultural, organizational and individual barriers that women entrepreneurs may face. This study interviewed 23 women entrepreneurs who own small agro-industries in Tasikmalaya district, a pilot project area for small agro-industry development in West Java. Our findings show that self efficacy is a common individual problem among rural women entrepreneurs, in addition to their suboptimal organizational capacity. Meanwhile, social and cultural barriers are currently minimal in rural areas. To improve self-efficacy, a personal approach is needed in the form of training, mentoring, and social support. Meanwhile, to improve organizational capacity, it is necessary to strengthen structural aspects such as management, technology, networking, and financing. We argue for the need to adopt more critical approaches, such as feminist discourse analysis and critical socio-technological perspectives to inform future research, and explain various phenomena related to women's entrepreneurship that have not been adequately studied.